Right with God : justification in the Bible and the world - Carson, D. A.; World Evangelical Fellowship. Faith and Church Study Unit. (Carlisle, UK : Paternoster Press ; Grand Rapids, Mich. : Baker Book House, 1992)
Pubished on behalf of the World Evangelical Fellowship.
Introduction / D.A. Carson -- The Biblical doctrine of justification by faith / Edmund P. Clowney -- Justification in Pauline thought / Brian C. Wintle -- Justification in Paul and some crucial issues of the last two decades / P.T. O'Brien -- Seek God's righteousness : righteousness in the Gospel of Matthew / Norvald Yri -- Justification in Luke-Acts / Richard B. Gaffin, Jr. -- Justification in the Gospel of John / Andrew H. Trotter -- Justification in the Epistle of James / Ronald Y.K. Fung -- Justification and personal Christian living / Russell Shedd -- Justification and social justice / Guillermo W. Mendez -- Justification and Roman Catholicism / Klaas Runia -- Justification by faith : its relevance in Hindu context / Sunand Sumithra -- Justification by faith : its relevance in Islamic context / Chris Marantika -- Justification by faith : its relevance in Buddhist context / Masao Uenuma.
"Published on behalf of the World Evangelical Fellowship."
Includes bibliographical references (p. [256]-302) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Justification (Christian theology) -- Biblical teaching; Justification (Christian theology) -- Comparative studies; Christianity -- Salvation